Effects Of Administration Of Poc Waste Of Snack Fish And Zpt Hantu On Production And Growth Of Peanut (Vigna Cylindrica L) - Prastari, Cindytia; Diana Syafni; Tengku Muhammad Ghazali (JURAGAN - Jurnal Agroteknologi, 2024)
Long bean plants (Vigna cylindrica L), one type of long bean horticultural plant, are a source of vitamin C and minerals. Long bean production in Pekanbaru is not yet optimal, many factors cause low long bean production. One of them is the Red and Yellow Podzolic land which is majority owned by Pekanbaru. PMK soil is a type of soil that has poor physical, chemical and biological properties, so it requires the addition of ameliorant substances such as manure. The aim of this research was to determine the effectiveness and obtain the best dose of the interaction of liquid organic fertilizer from snakehead fish waste and ghost growth regulator (ZPT) on the growth and production of long bean plants.The research was carried out on land at the Faculty of Agriculture, Riau University, 16 meters above sea level, with flat tropography with Red and Yellow Podzolic soil (PMK). This research was conducted for 2 months, starting from January to February 2023. This research was carried out experimentally using a factorial Completely Randomized Design (CRD), which consists of two factors, namely P (Liquid Organic Fertilizer), consisting of 3 levels, and the factor Z (Ghost ZPT) 3 replications, the number of experimental units was 27 plots, each plot consisted of 4 plants and 2 plants as samples, so that the total plants were 27 x 4 = 108 plants.Based on the results of research that has been carried out on the interaction of giving Snakehead Fish Waste Liquid Organic Fertilizer and Ghost Growth Regulator (ZPT) on the growth and production of long bean plants, it can be concluded that the interaction of giving Cow Manure and Hantu ZPT has a significant effect on the parameters of flowering age, stem diameter, number of fruits, and fruit length. Meanwhile, the fruit weight parameter had no significant effect. The best treatment interaction is P2Z2 with a dose of Liquid Organic Fertilizer of 10 ml/plot and giving Ghost ZPT 4 ml/l.